SPECIES DIVERSITY ASSESSMENT OF MAMMAL IN DOIMUKH REGION OF ARUNACHAL PRADESH - AND DANIEL MIZE, ABPREZ THUNGWON KIMSING, RENGNONG ZONGSAM (The Bioscan, 2018)
The present work is to investigate and record the mammal diversity in Doimukh area of Arunachal Pradesh. A total of 30 species of mammals belonging to 18 families under 9 orders were recorded during the study period between 2013 and 2014.The survey has been carried out following the line transect and other secondary methods. Of the total recorded,Carnivora and Rodentia were the most dominant order with 9 species each,followed by Artiodactyla with 5 species, Primates with 2 species, Proboscidea, Eulipotyphla,Lagomorpha, Pholidota and Chiroptera with 1 species each. Three species of squirrel namely Hoary-bellied himalayan squirrel, Himalayan striped squirrel and Pallas’s squirrel were the frequently observed mammals during the survey. From the recorded list,8 species were found to be threatened species under categoryas perIUCN Redlist, 2014.These includes 5 vulnerable species(Bos frontalis, Ursus thibetanus,Rusa unicolor,Pardofelis marmorata and Nycticebus bengalensis) and 3 endangered species (Elephas maximus, Cuonalpinus and Manis pentadactyla).2 large-sized, 1 mediumsized and 6 small-sized carnivores were recorded during the survey. The finding will provide baseline information for further systematic studies on mammals in the area.